THE KOMBINASI MICROWAVE DIATHERMY (MWD), ULTRASOUND (US) DAN STRETCHING SAMA BAIK DENGAN KOMBINASI MICROWAVE DIATHERMY (MWD), ULTRASOUND (US) DAN MYOFASCIAL RELEASE TECHNIQUE TERHADAP PENURUNAN TENSION TYPE HEADACHE (TTH) - Wismita, Luh Gde Eka; Putra, I Nyoman Adi; Nurmawan, Putu Sutha (Majalah Ilmiah Fisioterapi Indonesia, 2015)
This study was conducted to determine the effect of the difference between giving Microwave Diathermy, Ultrasound and Stretching with Giving Microwave Diathermy, Ultrasound and Myofascial Release Technique to decrease Tension Type Headache. This study is a pre - post test one group design with form 2 groups of unpaired (unrelated). The sample used 22 samples of patients with TTH, divided into 2 treatment groups. Treatment group I was given MWD, US and Stretching. MWD, US and Myofascial Release Technique. Each group a total of 11 samples. Analysis obtained by comparing the difference in mean VAS score CommittingGroup I and Group II treatment showed a p-value = 0.075, for p > 0.05 then there is no significant difference in VAS values between Group I and Group Treatment Treatment II. The conclusion of this study is the effect of the intervention MWD, US and stretching to decrease TTH. There is the effect of the intervention MWD, and Myofascial Release Technique US to decrease TTH. And there were no significant differences between the MWD,US and stretching with interventions MWD, US and Myofascial Release to decrease Tension Type Headache ( TTH ).
Keywords: MWD, US, Stretching, Myofascial Release Technique, Tension Type Headache (TTH)